Historical and cultural formation, evolution and ideological direction of Russian emigration literature - Aghamirzayev, Alish Choban (Technium Social Sciences Journal, 2021)
The article examines the formation of Russian émigré literature as a historical and cultural necessity at the beginning of the 20th century, the factors that contributed to its formation, the development of Russian émigré literature in the 20th century, its features, the ideological and political orientation of the "waves" of Russian émigré literature. It is shown that after the October Revolution of 1917, when the Bolsheviks came to power in Russia, pressure on free literature began, and the intelligentsia, which did not accept the dominant proletarian ideology, began to emigrate. Organized in exile, continuing the traditions of Russian classical literature, they laid the foundation for a new literary event in world literature - Russian émigré literature. The features of all three waves of Russian émigré literature, methods of literary struggle are given. Emigrant writers considered the main task of emigration to preserve national and moral values, historical memory and prevent its destruction among generations by preserving national identity. On the other hand, they considered it their duty to acquaint the world with the achievements of Russian public opinion and culture. For immigrant intellectuals who acted as bearers and defenders of Russian culture, the main criterion at all times was the preservation of Russian national and spiritual values, serving the Russian idea. Serving the Russian idea, saving and developing this one, drowned in the "shackles" of Soviet ideology, turned out to be their historical mission.